Self Regulation Santri Penghafal Alquran Usia Sekolah Dasar - Kharis Sulaiman Hasri; Suyadi Suyadi (Jurnal Psikologi Islam dan Budaya, 2020)
The purpose of this study is to explore self-regulation of Alquran memorizers in elementary school age. This study used a qualitative method with a phenomenological approach. The participants were collected using purposive sampling, which consisted of six students, five parents, and one teacher. The data collection instrument used semi-structured in-depth interviews and observation guidelines. The data were analyzed using the theory of Miles and Huberman with the stages of reduction, presentation, and conclusion. The self-regulation of elementary school students who memorize the Alquran is still guided by their parents both in setting goals, motivation and aspects of affection. In achieving goals, it is also influenced by the motivational aspects which are dominated by transcendental motivation. Meanwhile, the affection aspect occurs in a transition process from extrinsic motivation to intrinsic motivation.